Philippine choral music a conductor's guide to selected works composed between 1900 and 2010 - Yanson, Eliezer Garanchon (Ann Arbor, Mich. Proquest, 2010)
This research, geared towards the choral conductor and music educator, provides historical information on Philippine choral traditions, a discussion of performance practice, and a guide to Philippine diction. An important aspect of this research is an annotated choral works list, both published and unpublished, on selected Philippine choral literature. This list aims to help the discriminating conductor choose from a wide array of literature for concert programming. Among the compositions featured are the masterworks of Marcelo Adonay, Lucio San Pedro, Felipe de Leon, Lucrecia Kasilag, Jose Maceda, Francisco Feliciano, Ramon Santos, Josefino Toledo, Federico Razon, Ryan Cayabyab, John Pamintuan, and Nilo Alcala.
Submitted in partial fulfillment of the requirements for the Degree of Doctor of Musical Arts in the School of Music University of South Carolina, 2010.
Keywords: Choral music -- Philippines -- History and criticism